Temperature and flow data from a sediment tank experiment and numerical Advection-Dispersion Model code - Charles Luce; Daniele Tonina; Timothy DeWeese (PANGAEA, 2017)
To test revised theory for estimating fluid fluxes from temperature time series, we employed laboratory measurements and numerical modeling. Temperature and flow measurements were taken from a 40 cm X 40 cm Plexiglas tank filled with water and send. Full details of the experiment apparatus and procedure are provided in the associated text. Here we provide the flow rate data from a tipping bucket record and temperature time series from the water above the sand, and 2.97 cm into the sand. In addition we provide the code for a numerical (forward-time central-space) advection-dispersion model using a simple sinusoidal upper boundary condition along with code using a fast Fourier Transform to extract system parameters.
Supplement to: Luce, Charles; Tonina, Daniele; Applebee, R; DeWeese, Timothy (2017): Was that assumption necessary? Reconsidering boundary conditions for analytical solutions to estimate streambed fluxes. Water Resources Research, 53(11), 9771-9790, https://doi.org/10.1002/2017WR020618